Island spider origins show complex vertical stratification patterns in Macaronesia - Costa, R. (2023)
Spiders are among the most diverse and yet threatened groups of arthropods in Macaronesia. Found in most habitat types, they occupy the vertical gradient of native forests from ground to canopy level. We hypothesize that their vertical distribution is influenced by the colonization origin. As introduced species should arrive using shipping containers and similar means, they should mostly occupy the lower levels in the gradient, with potential negative effects on the indigenous epigean fauna. Spiders were sampled from epigean to arboreal microhabitats (maximum height varying between 2 and 4 m) on 45 sites across five islands belonging to three archipelagos. The mean and range of vertical stratification were obtained for each captured species. These values were then compared between different colonization origins at Macaronesian and archipelagic levels. Native non-endemic species were found at significantly higher vertical strata than both endemic and introduced species. Likewise, native non-endemics had a larger vertical range. These patterns were largely replicated across archipelagos, although there were exceptions. Overall, introduced species do not seem to occur mostly at lower strata in the native forests of Macaronesia (at least in the studied vertical range) but seem to be vertically restricted in most settings with the exception of Madeira.